Gagasan Membangun Potensi Anak Dalam Pembelajaran Outdoor (Eduscotech, 2023)
The outdoor study method is a learning method that invites students to study outside the classroom by utilizing the environment around the school for learning activities. This method can create an active student learning atmosphere, so it is necessary to choose the right method so that student activity can be raised. There are two reasons why outdoor play is used for learning in PAUD. First, many children's abilities must be developed. Second, busy parents always provide computer games, or watching television, causing children to stay away from playing activities. Outdoor play is a game given to early childhood by playing and learning to introduce nature and using various natural areas in nature so that children can observe natural objects around them and will get a unique experience. Outdoor learning can improve children's endurance, balance and body coordination. As well as various aspects of development such as social emotional, cognitive, and physical.